Late Bilinguals Are Sensitive to Unique Aspects of Second Language Processing: Evidence from Clitic Pronouns Word-Order - Rossi, Eleonora; Diaz, Michele; Kroll, Judith F.; Dussias, Paola E. (Frontiers in Psychology, 2017)
In two self-paced reading experiments we asked whether late, highly proficient, English-Spanish bilinguals are able to process language-specific morpho-syntactic information in their second language (L2). The processing of Spanish clitic pronouns’ word order was tested in two sentential constructions. Experiment 1 showed that English-Spanish bilinguals performed similarly to Spanish-English bilinguals and revealed sensitivity to word order violations for a grammatical structure unique to the L2. Experiment 2 replicated the pattern observed for native speakers in Experiment 1 with a group of monolingual Spanish speakers, demonstrating the stability of processing clitic pronouns in the native language. Taken together, the results show that late bilinguals can process aspects of grammar that are encoded in L2-specific linguistic constructions even when the structure is relatively subtle and not affected for native speakers by the presence of a second language.